Pelvic Floor Rehabilitation in Posttraumatic Masturbatory Syndrome - Arati Mahishale; Javiriya Mainuddin; Vikram Prabha (Archives of Medicine and Health Sciences)
Traumatic masturbation is characterized as a behavior that involves lying on the bed in a prone posture and stroking penis on the bed, pillow, or hands. This sort of behavior further causes sexual dysfunction and pelvic floor dysfunction. A significant concern is the use of physiotherapy in traumatic masturbatory syndrome (TMS) to treat pelvic floor dysfunction. This is a case study of a 34-year-old male with a complaint of inability to void urine adequately, with decreased urine output and straining during defecation secondary to TMS. The patient was screened using Dyssynergic dysfunction scale and Patient Assessment of Constipation–Quality of Life questionnaire, after which the patient was provided with physiotherapeutic intervention using Pelvic Floor Rehabilitation Protocol in Post TMS. The study concluded that Pelvic Floor Rehabilitation Protocol in post-TMS was found effective in the reduction of the pelvic floor muscle dysfunction.